(untitled) (Orfeu, 2026)
This article presents a musical analysis of Noturno depois do vinho by Tim Rescala through the Intertextual Compass — a conceptual tool that proposes an original systematization of intertextuality in the field of music. The work was chosen because it was entirely composed through the use of intertextuality, encompassing all nine main typologies of the Intertextual Compass and most of the others. The analysis details how the piece articulates style and intertextuality as central musical parameters, showing that each fragment derives from intertextual manipulations of four nocturnes by Chopin. It is concluded that Noturno depois do vinho constitutes a unique example of the practical application of the theories of the Intertextual Compass, revealing the creative potential of intertextuality as a compositional tool and reaffirming the research proposal as a means of consciously systematizing and expanding its use in musical creation processes.